2012
DOI: 10.1186/1758-2555-4-39
|View full text |Cite
|
Sign up to set email alerts
|

Humeral head osteonecrosis in an adolescent amateur swimming athlete: a case report

Abstract: Osteonecrosis of the humeral head in an adolescent without clear pathogenesis has not been reported in the literature. In this case report, we present such a case of humeral head osteonecrosis in a 15-year-old adolescent. The lesion was located at the subchondral area of the medial part of the humeral head with characteristic appearances on MRI. The shoulder was immobilized in a sling until the pain disappeared, and the patient was told to refrain any kind of sport activities. Bone remodeling was noted five mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Conservative treatment options can be effective in patients with Cruess grade I and II osteonecrosis [23, 27]. In this systematic review, the focal point was surgical treatment options, which are mainly indicated for high‐grade (III–V) osteonecrosis, but they are sometimes also performed in patients with grade II osteonecrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatment options can be effective in patients with Cruess grade I and II osteonecrosis [23, 27]. In this systematic review, the focal point was surgical treatment options, which are mainly indicated for high‐grade (III–V) osteonecrosis, but they are sometimes also performed in patients with grade II osteonecrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Pin site infection can be a common complication of percutaneous pinning but rarely leads to osteomyelitis of the humeral head. 52,53 In children, avascular necrosis of the humeral head is a rare complication due to the rich periosteum and blood supply compared to adults. Hutchinson et al demonstrated higher complication rates in the percutaneous pinning group up to 41% due to pin tract infections and pin migration.…”
Section: Patient Outcomesmentioning
confidence: 99%